Jenis dan Kelimpahan Mikroplastik pada Air Laut Pantai Lamaru Kecamatan Balikpapan Timur Provinsi Kalimantan Timur - Sarita, Greselia; Mustakim, Moh; Rafii, Akhmad (Fakultas Perikanan dan Ilmu Kelautan, 2023)
Microplastics have attracted worldwide attention because of their potential threat to marine ecosystems. The purpose of this study was to determine the abundance and types of microplastics on Lamaru beach. Studies were conducted on the abundance, size and composition of microplastics in seawater. The types of microplastics in the seawater at Lamaru beach are fiber, fragments and films. The total abundance of microplastics in the seawater at Lamaru beach is 4,434 particles/L. Fragments are the most common type of microplastic found in the coastal waters of Lamaru (3,036 particles/L), followed by films (834 particles/L), and fiber (564 particles/L). The results of statistical data analysis using the Kruskal-wallis test showed that there was no significant difference between types of microplastic and its values is Pvalue ((0,179 >α (0,05)). Microplastics are known to originate from seawater currents from the Makassar Strait and industrial activities around the coast.